ASSOCIATION OF RULA AND UPPER LIMB MUSCULOSKELETAL PAIN IN FINE ARTS STUDENTS - MATEEN , A; NADIR , F; QASIM , F; ALTAF , F; IMTIAZ , R; FATIMA , K; IRFAN , M; BUTT , AF; RAFIQUE , H; ASLAM , I (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to investigate the relationship between RULA and upper limb musculoskeletal pain in fine arts students. The research was conducted in Lahore, Pakistan, and involved 250 students from various universities, including NCA, BNU, PU, and GC University. To assess ergonomics, RULA was used, while the Nordic Musculoskeletal Questionnaire (NMQ) was used to evaluate pain. The data was analyzed using SPSS v20, and the Chi-square test was used to determine the association between RULA and upper limb musculoskeletal pain. The results revealed that shoulders were the most common area of pain reported by students in the last 12 months (68%) and last 7 days (60%), followed by wrist/hand pain (66% and 55.2%, respectively). The Chi-square value showed a significant association between RULA Score and Shoulder Pain (p-value 0.04) and RULA Score and Wrist Pain (p-value 0.05); however, there was no significant association between RULA and Elbow pain (p-value 0.861). Statistical significance was set at p-value ≤ .05. In conclusion, this study found a significant association between RULA and upper limb musculoskeletal pain in fine arts students.